Group antenatal care positively transforms the care experience: Results of an effectiveness trial in Malawi - Crystal L. Patil; Kathleen F. Norr; Esnath Kapito; Li C. Liu; Xiaohan Mei; Elizabeth Chodzaza; Genesis Chorwe-Sungani; Ursula Kafulafula; Elizabeth T. Abrams; Allissa Desloge; Ashley Gresh; Rohan D. Jeremiah; et al. (PLoS ONE, 2025)
Background We developed and tested a Centering-based group antenatal (ANC) model in Malawi, integrating health promotion for HIV prevention and mental health. We present effectiveness data and examine congruence with only the Group ANC theory of change model, which identifies key processes as supportive relationships, empowered partners in learning and care, and meaningful services, leading to better ANC experiences and outcomes. Methods We conducted a hybrid effectiveness-implementation trial at seven clinics in Blantyre District, Malawi, comparing outcomes for 1887 pregnant women randomly assigned to Group ANC or Individual ANC. Group effects on outcomes were summarized and evaluated using t-tests, Mann-Whitney, or Chi-squared tests. Adjusted for seven individual and two clinic-level baseline covariates, point estimates are reported for continuous outcomes using multivariable linear regression models. Adjusted for the same covariates, odds ratios are reported for categorical outcomes using logistic regression models. All statistical tests were two-sided, controlling for a Type I error probability of 0.01 due to multiple testing. Findings Women in Group ANC had higher peer connectedness and pregnancy-related empowerment, recalled receiving more services, and discussed more health promotion topics. They experienced less wait time, greater satisfaction with care (Estimate = 1.21, 99% CI = 0.07, 2.35), and had a higher mean number of ANC contacts (Estimate = 0.74, 99% CI = 0.50, 0.98). Most women preferred Group ANC for a future pregnancy (81% in Individual ANC; 95% in Group ANC). Women in Group ANC had more diverse diets (Estimate = 0.35, 99% CI = 0.17, 0.53), were better prepared for birth (Estimate 0.32, 99% CI = 0.16, 0.48), more likely to use condoms consistently (OR= 1.07, 99% CI = 1.00, 1.14) and communicated more with partners. They reported less mental distress in late pregnancy (Estimate = −0.61, 99% CI = −1.20, −0.02). Exclusive breastfeeding, partner HIV testing and disclosure, facility-based delivery, postnatal care attendance, postpartum family planning, and low birth weight did not differ by ANC type. Conclusions This effectiveness study of Malawi Group ANC, the first trial with individual randomization in a low-income country, maps outcomes to the theory of change, enhancing our understanding of Group ANC’s diverse positive impacts. The integration of typically neglected health promotion topics into the model highlights its flexibility to address changing local and global needs. Based on study results, the Malawi Ministry of Health is introducing Group ANC at district-level trainings and exploring the logistics for nationwide adoption. With momentum and political will, better care and a positive healthcare experience can be achieved for women, infants, and families in Malawi and globally. Trial registration ClinicalTrials.gov NCT03673709 .